(untitled) (International journal of artificial intelligence, 2026)
Professional motivation is considered one of the most important psychological factors determining the effectiveness of educators’ pedagogical activity. In modern educational systems, the professional success of educators depends not only on their knowledge and skills, but also on their internal motivation, psychological readiness, emotional stability, and commitment to professional development. This article analyzes the psychological foundations of professional motivation in educators, the factors influencing motivational processes, and the role of intrinsic and extrinsic motivation in pedagogical activity. The study also examines scientific approaches developed by foreign and local researchers regarding professional motivation and highlights the importance of psychological support in increasing educators’ professional efficiency. Furthermore, the article discusses the impact of professional self-awareness, emotional resilience, job satisfaction, social recognition, and working conditions on educators’ motivation. The findings show that professionally motivated educators demonstrate higher pedagogical effectiveness, creativity, responsibility, and emotional stability in educational environments. The article concludes that strengthening professional motivation through psychological and organizational support is essential for improving the quality of education.